IMPLEMENTATION OF GENRE-BASED EFL WRITING: CLASSROOM REALITIES IN A VOCATIONAL MUSIC SCHOOL - Muhammad Ra'is Zhaliifunnas; Rahmi Munfangati (Universitas Islam Sumatera Utara (UISU), 2026)
This study investigates the implementation of the Genre-Based Approach (GBA) in EFL writing instruction at a vocational music senior high school, focusing on the challenges teachers face in classroom practice. A qualitative case study design was employed, with data collected through classroom observations, in-depth interviews with an English teacher, and document analysis. Thematic analysis was used to identify patterns related to instructional practices, scaffolding strategies, and contextual constraints. GBA was implemented through its core pedagogical stages from Building Knowledge of the Field (BKOF) to Independent Construction of Text (ICOT) in alignment with its theoretical framework. However, implementation was constrained by several interrelated challenges, including limited instructional time, heterogeneous beginner-level proficiency, and restricted technological resources. In response, the teacher employed adaptive strategies such as flexible scaffolding, differentiated instruction, collaborative learning, bilingual explanations, and the use of artificial intelligence. Flexible scaffolding and bilingual explanations, in particular, enabled students to produce genre-appropriate texts despite their limited proficiency. The findings reveal a persistent gap between the idealized conceptualization of GBA and its actual realization in classroom practice. Effective GBA implementation requires pedagogical flexibility and contextual awareness, not rigid adherence to procedural implementation. This study enriches empirical GBA research by illustrating how teachers negotiate its principles under non-ideal classroom conditions.